2002
DOI: 10.1007/s00239-001-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Phylogenetic Analysis of the cAMP-Dependent Protein Kinase Regulatory Subunit Family

Abstract: Abstract. The members of the PKA regulatory subunit family (PKA-R family) were analyzed by multiple sequence alignment and clustering based on phylogenetic tree construction. According to the phylogenetic trees generated from multiple sequence alignment of the complete sequences, the PKA-R family was divided into four subfamilies (types I to IV). Members of each subfamily were exclusively from animals (types I and II), fungi (type III), and alveolates (type IV). Application of the same methodology to the cAMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
104
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 52 publications
4
104
0
Order By: Relevance
“…Results Sequence Structure Analysis. As shown previously (1,4,12), sequences of CNB-containing domains found in many organisms are well aligned. Structural analyses confirmed that secondary structure assignments are also very similar to what is seen in Fig.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…Results Sequence Structure Analysis. As shown previously (1,4,12), sequences of CNB-containing domains found in many organisms are well aligned. Structural analyses confirmed that secondary structure assignments are also very similar to what is seen in Fig.…”
Section: Methodssupporting
confidence: 72%
“…1 b and c) where glutamic acid and arginine residues form specific hydrogen bonds with the O2Ј of the sugar and the O1P of the phosphate (1,12). These hydrogen bonds anchor the cAMP in a hydrophobic environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As organismal complexity increases, so theoretically does the requirement for an increased complement of signal transduction machinery. Whereas expansion of some kinase families appears to parallel increasing organismal complexity (1), the protein kinase A family has undergone little expansion (2) despite the large number of its physiological substrates distributed throughout the cell. Thus, intrinsic differences between protein kinase A family members cannot fully account for such diversity because, on their own, they do not provide sufficient specificity.…”
mentioning
confidence: 99%
“…Mutagenesis (7) and hydrogen/deuterium exchange experiments (8) have identified the helical subdomain in the more N-terminal cAMP-binding domain (domain A) of RI␣ as an additional region of contact between the R and C subunits. There is high sequence homology between the isoforms in the D/D domain and the cAMPbinding domains, but the linker regions are quite different in length and sequence (9).…”
mentioning
confidence: 99%